Mechanically alloyed Sm-Co hard magnetic materials - Gallagher, Kathleen (Trinity College (Dublin, Ireland). School of Physics, 2002)
In the recent search for new high-temperature permanent magnet materials, research has concentrated on bulk Sm2Co17-type magnets. The usual approach to development of coercivity in bulk Sm-Co based materials is to prepare a nanophase cellular microstructure with cell walls that act as pinning sites (precipitation hardening). An alternative approach is to mechanically alloy the materials, with the goals of reducing particle size, forming metastable phases, and introducing planar crystalline defects that act as pinning sites. The objectives of this work were to produce SmZr(Co,Fe) alloys by mechanical alloying, to study the effect of composition on magnetic properties, and to assess whether these materials would make good high temperature magnets. In this work, SmzZry(Co1-xFex)100-z-y nanocrystalline powders, where 13 ≤ z ≤ 15, 0 ≤ y ≤ 5, and 0 ≤ x ≤ 0.5 (compositions intermediate to SmCo5 and Sm2Co17), were prepared by mechanical alloying followed by an optimized annealing procedure. Powder particles were roughly spherical and ranged in size from a few micrometers in size up to 20 μm. X-ray diffraction patterns showed that the as-milled powders were amorphous, or had some very small α-Fe crystallites < 10 nm in size, depending on composition. Annealed samples showed a mixture of Sm2Co17 (Th2Ni17 and Th2Zn17 structures) and SmCo5 nanocrystalline phases, in relative amounts dependent on composition. Substitution of Fe increases the grain size and favors the formation of Sm2Co17. Addition of Zr has the opposite effect: it decreases the grain size and favors the formation of SmCo5. Room temperature hysteresis loops for all compositions studied show smooth demagnetization curves and enhanced remanence (σr/σs> 0.60) is achieved in all compositions, indicating intergrain exchange coupling among the fine grains. Coercivity peaks in all Smx(Co1-zFez)100-x for z = 0.1, and hence Fe content was fixed at z = 0.1 for studies of Zr substitution. With Zr content, coercivity increased, probably due to a decrease in grain size and an increase in the amount of SmCo5 phase present. Increased Zr content caused remanence and energy product to decrease. Maximum room temperature coercivity of 1.74 T is obtained in the composition Sm14Zr3(Co0.9Fe0.1)83, while a maximum energy product of 100 kJ/m3 is achieved in Sm13Zr(Co0.9Fe0.1)86. A systematic investigation of magnetic properties in the temperature range 20ºC ≤ T ≤ 500ºC was carried out on compositions with x = 0.1, and various Sm and Zr contents. High temperature magnetic measurements show that the properties degrade irreversibly at temperatures above 300ºC. Loops taken at low temperature after measurement change from that of a single magnetic phase to that of a two-phase mixture. This behavior is attributed both to grain growth and to a phase change in the material at these temperatures. Finally, magnetization reversal in these materials was investigated through measurement of virgin magnetization, recoil, and magnetic viscosity, allowing calculation of Sv and activation volume, Va. Calculation of total susceptibility, χtot shows that these materials undergo a very sharp reversal, with the exception of the binary compound, which shows reversal of a small amount of soft material in low fields. Virgin curves and plots of reversible magnetization vs. irreversible magnetization show that there is actually very little pinning in the materials. Unlike bulk Sm2(Co, Fe, Cu, Zr)17-type pinning-controlled materials, these materials have a nucleation controlled nature. Calculated Va for mechanically alloyed Sm14Zr(Co0.9Fe0.1)85 is larger than the activation volume for commercial Sm2(Co, Fe, Cu, Zr)17 materials. This is because, in the absence of pinning sites, a larger volume of materials is involved in the reversal. In the recent search for new high-temperature permanent magnet materials, research has concentrated on bulk Sm2Co17-type magnets. The usual approach to development of coercivity in bulk Sm-Co based materials is to prepare a nanophase cellular microstructure with cell walls that act as pinning sites (precipitation hardening). An alternative approach is to mechanically alloy the materials, with the goals of reducing particle size, forming metastable phases, and introducing planar crystalline defects that act as pinning sites. The objectives of this work were to produce SmZr(Co,Fe) alloys by mechanical alloying, to study the effect of composition on magnetic properties, and to assess whether these materials would make good high temperature magnets. In this work, SmzZry(Co1-xFex)100-z-y nanocrystalline powders, where 13 ≤ z ≤ 15, 0 ≤ y ≤ 5, and 0 ≤ x ≤ 0.5 (compositions intermediate to SmCo5 and Sm2Co17), were prepared by mechanical alloying followed by an optimized annealing procedure. Powder particles were roughly spherical and ranged in size from a few micrometers in size up to 20 μm. X-ray diffraction patterns showed that the as-milled powders were amorphous, or had some very small α-Fe crystallites < 10 nm in size, depending on composition. Annealed samples showed a mixture of Sm2Co17 (Th2Ni17 and Th2Zn17 structures) and SmCo5 nanocrystalline phases, in relative amounts dependent on composition. Substitution of Fe increases the grain size and favors the formation of Sm2Co17. Addition of Zr has the opposite effect: it decreases the grain size and favors the formation of SmCo5. Room temperature hysteresis loops for all compositions studied show smooth demagnetization curves and enhanced remanence (σr/σs> 0.60) is achieved in all compositions, indicating intergrain exchange coupling among the fine grains. Coercivity peaks in all Smx(Co1-zFez)100-x for z = 0.1, and hence Fe content was fixed at z = 0.1 for studies of Zr substitution. With Zr content, coercivity increased, probably due to a decrease in grain size and an increase in the amount of SmCo5 phase present. Increased Zr content caused remanence and energy product to decrease. Maximum room temperature coercivity of 1.74 T is obtained in the composition Sm14Zr3(Co0.9Fe0.1)83, while a maximum energy product of 100 kJ/m3 is achieved in Sm13Zr(Co0.9Fe0.1)86. A systematic investigation of magnetic properties in the temperature range 20ºC ≤ T ≤ 500ºC was carried out on compositions with x = 0.1, and various Sm and Zr contents. High temperature magnetic measurements show that the properties degrade irreversibly at temperatures above 300ºC. Loops taken at low temperature after measurement change from that of a single magnetic phase to that of a two-phase mixture. This behavior is attributed both to grain growth and to a phase change in the material at these temperatures. Finally, magnetization reversal in these materials was investigated through measurement of virgin magnetization, recoil, and magnetic viscosity, allowing calculation of Sv and activation volume, Va. Calculation of total susceptibility, χtot shows that these materials undergo a very sharp reversal, with the exception of the binary compound, which shows reversal of a small amount of soft material in low fields. Virgin curves and plots of reversible magnetization vs. irreversible magnetization show that there is actually very little pinning in the materials. Unlike bulk Sm2(Co, Fe, Cu, Zr)17-type pinning-controlled materials, these materials have a nucleation controlled nature. Calculated Va for mechanically alloyed Sm14Zr(Co0.9Fe0.1)85 is larger than the activation volume for commercial Sm2(Co, Fe, Cu, Zr)17 materials. This is because, in the absence of pinning sites, a larger volume of materials is involved in the reversal.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin